Communication, Informational Literacy and Critical Thinking - Cardoso, Luís Miguel; Nuno Moura Silva (European Journal of Multidisciplinary Studies, 2018)
Being a citizen with literacy skills is fundamental. Nowadays we live in network and in the network. However, the fact that everything can be shared online entails some risks - both for users and for authors.. In order to deal with massive information and communication channels, having the competence and insight to be able to search and select the most credible information is a requirement and a fundamental competence in a networked society. In this paper we will reflect upon the concepts of communication, cyberculture, information literacy and critical thinking. In conclusion, it is demonstrated that information literacy is a key competence in contemporary society.